Genetic analysis of yield related traits in 5×5 diallel crosses of spring wheat (Triticum aestivum L.) (Journal of Agriculture and Biology, 2023)
Wheat, a staple crop and an essential component of global food security, holds immense significance for Pakistan due to its historical roots, agricultural contributions, and socio-economic impact. The present study was conducted to reveal the genetics of various yield associated traits in spring wheat using 5 × 5 diallel cross scheme involving high yielding wheat varieties. A total of ten tillers per plant, 1000-grain weight, number of total grains per spike, peduncle length, length of spike, and yield of grain per plant were among the characteristics that were evaluated. Hybrid vigor can be a viable strategy for further improving these characteristics, as the graphical analysis for all characteristics per plant demonstrated supremacy form of gene activity. While additive action of gene with partial dominance dictated the transmission of peduncle length and number of tillers per plant, these features might be improved in early generations by selecting for attractive transgressive segregates. For all of the studied characteristics no epistasis was evaluated. This study is promising and has the potential to significantly impact wheat breeding programs, agricultural productivity, and food security in the coming years.